Short Communication: Molecular identification and assessment of bacterial contamination of frozen local and imported meat and chicken in Basrah, Iraq using 16S rDNA gene (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mohammad AJ, Alyousif NA. 2022. Short Communication: Molecular identification and assessment of bacterial contamination of frozen local and imported meat and chicken in Basrah, Iraq using 16S rDNA gene. Biodiversitas 23: 1598-1604. Meat is the main food source of daily meals with highly beneficial effects on human health. It is susceptible to the growth and reproduction of various bacteria due to its composition, which leads to its spoilage, and being an important carrier of pathogenic bacteria. The study aimed to isolate and identify the bacteria contamination of frozen local and imported meat and chicken samples using 16S rDNA gene. Twenty meat samples were collected randomly from local and imported meat sold in markets of Basrah province, Iraq. The results showed that the total aerobic bacteria count was within acceptable limits in all samples. Fifty-seven bacterial isolates were isolated and identified by amplification and sequencing of 16S rDNA gene, where the gram-positive bacteria were the most abundant 34(59.6%), and S. pasteuri is the most common species in the samples with 14 (24%) bacterial isolates out of the total isolates. Fifteen isolates were identified as new strains and their sequences were deposited at GenBank (NCBI) under different accession numbers (MZ964582-MZ964596). The meat and chicken have many bacteria on their surface, therefore the products must be frozen, and sanitary precautions should be taken into consideration.
Keywords: Bacterial contamination, food spoilage, PCR, Meat, Chicken